2009
DOI: 10.1017/s0266462309990341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge network for medical technology management in Mexico

Abstract: This network has led us to propose this approach to solve medical technology management projects, where the strengths of each subgroup complement each other. This structure will lead to a more integrated approach to healthcare technology management and will ensure higher quality solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“… 28 However, committees are not flawless; Licona et al described a case study to demonstrate involvement of an interdisciplinary network of professionals in health technology management: despite the involved network several anomalies were identified such as uncertainty of who would install equipment after a bidding process. 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 However, committees are not flawless; Licona et al described a case study to demonstrate involvement of an interdisciplinary network of professionals in health technology management: despite the involved network several anomalies were identified such as uncertainty of who would install equipment after a bidding process. 29 …”
Section: Resultsmentioning
confidence: 99%
“… 39 Licona et al describe several iterations in the specification process to avoid last minute changes, and discuss that stringent specifications may lead to the selection of products with the lowest technical and qualitative requirements. 29 In another study, less stringent tender specifications actually showed to lead to substantial cost savings: instead, an iterative negotiation process with multiple vendors after a broad request for proposals led to an aggressive form of competition with varying strategies to form a solution. 44 Finally, there appears to be a reciprocity between industry and hospitals: as clinical trials with equipment have the potential to deliver evidence of functionality for devices, healthcare and industry are incentivised to cooperate in creating and obtaining this evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Licona et al ( 2009) describe several iterations in the specification process to avoid last minute changes, and discuss that stringent specifications may lead to the selection of products with the lowest technical and qualitative requirements. [35] In another study, less stringent tender specifications actually showed to lead to substantial cost savings: instead, an iterative negotiation process with multiple vendors after a broad request for proposals led to an aggressive form of competition with varying strategies to form a solution. [26] Finally, there appears to be a reciprocity between industry and hospitals: as clinical trials with equipment have the potential to deliver evidence of functionality for devices, healthcare and industry are incentivised to cooperate in creating and obtaining this evidence.…”
Section: Resultsmentioning
confidence: 99%
“…[28] However, committees are not flawless; Licona et al ( 2009) described a case study to demonstrate involvement of an interdisciplinary network of professionals in health technology management: despite the involved network several anomalies were identified such as uncertainty of who would install equipment after a bidding process. [35]…”
Section: Key Findings From Studiesmentioning
confidence: 99%